Bose-condensed gases at finite temperatures - Griffin, Allan (Cambridge University Press, 2009)
The discovery of Bose-Einstein condensation in trapped ultracold atomic gases in 1995 has led to an explosion of theoretical & experimental research on the properties of Bose-condensed dilute gases. This text presents a thorough account of the theory of two-component dynamics & non-equilibrium behaviour in superfluid Bose gases.